LO098: Education innovation: implementing a point-of-care ultrasound curriculum for emergency medicine residents. (2nd June 2016) - Leung, D.; Chenkin, J.
Abstract : Introduction / Innovation Concept: Point-of-care ultrasound (POCUS) is becoming standard of care in Canadian emergency departments. However, its integration in Emergency Medicine (EM) residency training is poorly studied. If a four-week curriculum can successfully teach POCUS skills to residents, this program could have potential application across specialties and across Canada.Methods: A four-week curriculum was designed, implemented, and evaluated. EM residents registered for the Introductory Ultrasound Rotation at Sunnybrook Health Sciences Centre were invited to participate. Curriculum evaluation included resident feedback, pre-rotation and post-rotation knowledge and skill testing, and a delayed post-rotation survey. Comparison of pre-test and post-test scores were calculated using the paired t-test.Curriculum, Tool, or Material: Residents were scheduled for both dedicated ultrasound scanning shifts and clinical shifts with an emphasis on POCUS in patient care. Residents also reviewed the Canadian Emergency Ultrasound Society Emergency Department Echo DVD and manual, completed weekly readings and assignments, and completed a "clinical encounter worksheet" describing how POCUS impacted clinical care in a patient encounter. Other rotation activities included Ultrasound Rounds where residents presented a critical appraisal of a POCUS-related journal article, Pediatric Ultrasound Rounds at The Hospital for Sick Children, and an advanced POCUS workshop day. Of 13 eligible residents, 12 (92%) completed at least one study assessment. However, only 8 residents (62%) completed both the pre-test and post-test, 8 residents (62%) completed the end-of-rotation survey, and even fewer residents (42%) completed the delayed post-rotation survey. Residents felt the quality of the ultrasound rotation was excellent (mean score 4.7 on 5-point Likert scale). There was an increase in test scores from a baseline of 51.5% to 70.8% on the post-rotation test (p=0.02). Three months after the rotation, 100% of residents reported feeling either comfortable or extremely comfortable teaching and using the core POCUS topics covered in the curriculum. All residents reported that they would recommend the rotation to their colleagues without hesitation. All residents passed the national ultrasound certification examination at the end of the rotation.Conclusion: A four-week curriculum was effective in teaching EM residents POCUS skills. Further study is required to determine the ideal method for teaching POCUS skills in this group.